HASIL PERTANIAN BUAH (MELON, SEMANGKA, JERUK, APEL) MENJADI OLAHAN SALAD BUAH - Asep Yudi Prasetia (Jurnal INDONESIA RAYA (Pengabdian pada Masyarakat Bidang Sosial, Humaniora, Kesehatan, Ekonomi dan Umum), 2025)
Indonesia as an agricultural country has great potential in the production of tropical fruits such as melons, watermelons, dragon fruits, oranges, and apples. However, the utilization of these agricultural products is often not optimal, mainly due to limited storage and distribution technology. This paper discusses the opportunity to process fruit agricultural products into fruit salad products as an innovative culinary business based on entrepreneurship. By utilizing local ingredients, fruit salad not only increases the added value of agricultural products but also meets consumer needs for healthy and practical food. Through effective marketing strategies, SWOT analysis, and product innovation, the business is able to face challenges such as market fluctuations and competition. The results of this activity show that the fruit salad business has promising prospects, especially in areas with low competition and high public awareness of healthy eating. This conclusion supports the development of agribusiness-based entrepreneurship to improve the welfare of local farmers and small business actors.